METHODICAL TOOLS OF THE ASSESSMENT AND ANALYSIS OF THE ACCEPTABILITY OF INVESTMENT PROJECTS - Tatiana A. Kulagovskaya; Nataliya G. Borodina (Вестник Северо-Кавказского федерального университета)
The article deal with the problems off an assessment of investment projects are considered, the making estimates of the acceptability of each investment project are analysed. The main attention is paid to methods of an assessment and the risk analyses arising in the course of implementation of investment projects